Deterministic, stochastic and fractional mathematical approaches applied to AMR - Sebastian Builes; Jhoana P. Romero-Leiton; Leon A. Valencia (Mathematical Biosciences and Engineering)
In this work, we study the qualitative properties of a simple mathematical model that can be applied to the reversal of antimicrobial resistance. In particular, we analyze the model from three perspectives: ordinary differential equations (ODEs), stochastic differential equations (SDEs) driven by Brownian motion, and fractional differential equations (FDEs) with Caputo temporal derivatives. Finally, we address the case of Escherichia coli exposed to colistin using parameters from the literature in order to assess the validity of the qualitative properties of the model.